(untitled) (Research, Society and Development, 2020)
This work aimed to evaluate the presence of the bioactive metabolites from sucupira seeds in prepared herbal medicines obtained by the immersion of the seeds in cachaça were evaluated by varying the physical-chemical characteristics of the cachaça used; the phytotherapic preparation method (extraction time of plant material) and storage conditions (with and without seeds immersed). The chemical profile of the extracts was determined GC-MS. The presence of some bioactive metabolites was observed, which were extracted with the cachaça of lower alcohol concentration (44.5%) after two months of contact with the seeds. These metabolites were not identified in samples stored for four months. The cachaça with an alcohol concentration of 46.5%, after 2 months of maceration, promoted the extraction of β-elemene, only and the others with contents of 48.5%, 49.5% and 50.4%, respectively, extracted the bioactive metabolites: spathulenol, D-germacrene, δ-cadinene, caryophylene and β-elemene in the maceration periods of 15 days and 2 months. In the extracts that were stored without seeds, the metabolites spathulenol and δ-cadinene were the only ones that remained present in all samples after two and four months of storage. The extraction of all metabolites was possible with the crushed and macerated seeds remaining for 2 months in cachaça with an alcohol content greater than 45%.